Inflation in motion: the effect of fuel prices on a dollarized economy, the case of Ecuador - Yaselga Alvarado, Emanuel Daniel (2025)
This paper examines the influence of fuel prices on inflation in Ecuador since 2015. Since 2018, Ecuador has implemented a series of measures on fuel prices, some linked to increased margins or liberalization througha banding system. This rise in fuel prices has had a significant effect on inflation directly related to transportation and has also spilled over into other inflation components. The study uses local projection methodology to assess the magnitude and duration of these price changes. The results indicate that the increase in WTI fuel prices had a significant, asymmetric impact on inflation—specifically, a positive WTI shock raises inflation, while a decrease does not have a comparable effect. We also identified additional transmission effects of diesel prices on transportation services.